Primary Headache Disorder Among School Students in Kuwait - Shuaibi, Sameera; AlAshqar, Abdelrahman; Ahmed, Samar Farouk; Alroughani, Raed; AlThufairi, Hawraa; Owayed, Shaikhah; AlHamdan, Fajer; Al-Hashel, Jasem (Frontiers in Neurology, 2021)
Background: Primary headaches are remarkably prevalent worldwide and increasingly reported among children. However, the exact trend in this age group, particularly in the gulf region, remains largely unknown. Aims and Objectives: To examine the prevalence of primary headache disorders among primary and middle school students in Kuwait. Methods: We conducted a cross-sectional study that included Kuwaiti primary and middle school children and adolescents of both genders in randomly selected schools located in two governorates in Kuwait in the 2018/2019 academic year. Prevalence and attributable burden of headache, definite and probable migraine, definite and probable tension-type headache, chronic headache (≥15 days/month), and probable medication over use headache were assessed using the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation (HARDSHIP) questionnaire for children and adolescents. Results: Of 1,485 questionnaires that were distributed, 1,089 students completed the questionnaire with a respondent rate of 73.4%. The study population consisted of 420 boys (38.56%) and 669 girls (61.43%) students with a mean age of 11.5 ± 2.11 years. The one-year prevalence of primary headache disorders was 42.78% with more middle schoolers reporting headaches than primary schoolers (50.37% vs 30,48%; p <0.02). The mean age of students with primary headaches was 11.98 ± 2.03 years in both genders. When stratified according to diagnostic criteria, migraine headaches were the most frequently reported (20.75%) followed by tension type headaches (18.8%), chronic headaches (2.75%), and probable medication-overuse headaches (0.46%.). Primary headaches were significantly higher in girls compared to boys among middle schoolers (66.46% vs 38.49%; p <0.001); however, no significant difference between genders was noted among primary school students (33.12% vs 22.33%; p <0.118). Conclusion: Primary headaches are remarkably common in Kuwaiti school students, with migraine headache being the most frequently reported type. Age and female gender may play a role in the development of primary headaches. These findings necessitate the direction of health services and research efforts towards this age group and warrant the need for further epidemiological studies.